A generalized HBV model with diffusion and two delays. (January 2015) - Hattaf, Khalid; Yousfi, Noura
Abstract An hepatitis B virus (HBV) model with spatial diffusion, general incidence rate and time delays subject to homogeneous Neumann boundary conditions is formulated. The stability of the disease-free equilibrium and the chronic infection equilibrium is analyzed by using the linearization method and by constructing appropriate Lyapunov functionals. Furthermore, several diffusive HBV models existing in the literature are generalized and extended.